Uptake of the IMMPACT-recommended core outcome set in randomised controlled trials on chronic neck or shoulder pain: a cross-sectional study - Guoliang Li; Lin Zeng; Siyan Zhan; Wenqiang Li; Jiaheng Shang (BMJ Open)
Objective To analyse the uptake rate of Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT)-recommended core outcome set (COS) in randomised controlled trials (RCTs) on chronic neck or shoulder pain and its potential influencing factors.Design A cross-sectional study.Setting WHO International Clinical Trials Registry Platform, involving 15 registries.Participants RCT registrations on chronic neck or shoulder pain.Primary outcome measures The uptake rate of IMMPACT-recommended COS in RCTs focusing on chronic neck or shoulder pain.Results A total of 1057 RCT registrations were included between 2 February 2004 and 8 February 2023. The most used domains were pain (n=1003, 94.9%) and physical functioning (n=971, 91.9%), while the remaining four core domains and supplementary domains received less attention (<10%), exhibiting either a downward trend or an initial increase followed by a decrease. Univariable and multivariable analyses did not indicate consistent, significant differences in various outcome domains in RCTs categorised according to the study period, blinding and prospective registration statuses, follow-up duration and sample size.Conclusions Although the pain and physical functioning domains were widely reported by RCTs on chronic neck or shoulder pain since the publication of IMMPACT-recommended COS, the uptake rate was low for other domains and outcome measures. The study period, blinding status, prospective registration, follow-up duration and sample size may influence COS uptake across domains.Trial registration number http://www.comet-initiative.org/Studies/Details/3213.